Tissue responsiveness to estradiol and genistein in the sea bass liver and scale - Estêvão, M. Dulce (2017)
As in mammals, estrogens in fish are essential for reproduction but also important regulators of mineral homeostasis. Fish scales are a non-conventional target tissue responsive to estradiol and constitute a good model to study mineralized tissues effects and mechanisms of action of estrogenic compounds, including phytoestrogens. The responsiveness to estradiol and the phytoestrogen genistein, was compared between the scales and the liver, a classical estrogenic target, in sea bass (Dicentrarchus labrax). Injection with estradiol and genistein significantly increased circulating vitellogenin (for both compounds) and mineral levels (estradiol only) and genistein also significantly increased scale enzymatic activities suggesting it increased mineral turnover. The repertoire, abundance and estrogenic regulation of nuclear estrogen receptors (ESR1, 2a and 2b) and membrane G-protein receptors (GPER and GPER-like) were different between liver and scales, which presumably explains the tissue-specific changes detected in estrogen-responsive gene expression. In scales changes in gene expression mainly consisted of small rapid increases, while in liver strong, sustained increases/decreases in gene expression occurred. Similar but not overlapping gene expression changes were observed in response to both estradiol and genistein. This study demonstrates for the first time the expression of membrane estrogen receptors in scales and that estrogens and phytoestrogens, to which fish may be exposed in the wild or in aquaculture, both affect liver and mineralized tissues in a tissue-specific manner. (C) 2015 Elsevier Ltd. All rights reserved.